BERNYANYI DAN BERGERAK DALAM IRAMA SEBUAH LAGU UNTUK BELAJAR KOSAKATA DI TAMAN KANAK-KANAK - Elma Eskarina; Lilia Indriani (Unika Santu Paulus Ruteng, 2021)
English language skills are expected to help children in the future to be able to interact globally and make it easier for them to establish relationships widely. One of the concerns in learning English is to build vocabulary in children through fun activities so that children do not feel that learning English is too boring and difficult. One of the methods used to introduce English to children is to use fun methods such as movements and songs which are usually done as a routine in class. This study aims to determine how the level of students' abilities and students' perceptions in improving English vocabulary after being given treatment using motion and song. This study used quantitative methods through pre-experimental design that utilizes pre-test and post-test to a group of students to determine their progress before and after being given treatment. Using the test would make an appropriate and accurate comparison to find out the improvement that occurs to students. The data collection technique was carried out by classroom observation at one of the Kindergartens that had compulsory English extracurricular. With the results in the post-test, the findings of this study were that early childhood children could have significant results after being given treatment. There were even children who can answer almost all the vocabulary in the ten designated objects. In addition, based on the responses of students who took part in the lesson they reveled this method with a thumbs up sign and a smile shown to the teacher. So it can be concluded that the motion and song method can be suitable methods for early childhood to introduce English.